(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2019)
The idea of change within the Latin American university took the form of development after the second postwar period. Before that, the colonial university, the republican university and the changes generated after the events of Cordoba, had defined the characteristics of the academic nature of what in general we can consider the university of Latin America. But, having begun the modernization processes in the continent, the central purpose of the higher institution changed, from that moment was to build, based on science, development. Accurate, but more inaccurate, have defined Venezuelan university education, to the point that for the 21st century we find ourselves outside the canons of regional competition. However, the potentialities still make it possible to visualize possible changes. The world discusses human development as an approach to building processes conducive to justice. Today, these ideas provide us with ethical tools to rethink the university. This paper is oriented in that way. Its purpose is to review the antecedents that shaped the university orientation of the country since the spanish colony, until the 21st century and then left a description of the Venezuelan university panorama, define dimensions that reformulate a concept of academic quality seen from the Human Development approach.